Analisis Peraturan Bupati No 27 Tahun 2021 tentang Pedoman Pencalonan, Pemilihan, Pengangkatan, Pelantikan, dan Pemberhentian Kepala Desa di Kabupaten Sampang (Studi Kasus Penundaan Pemilihan Kepala Desa di Kabupaten Sampang) - R. Zainul Mushthofa; Siti Aminah; Siropi Siropi (JOSH: Journal of Sharia, 2023)
The election of the village head is one of the most popular forms of a democratic party. This village-level election is an arena for political competition that is very effective if it can be used for political learning for the community. At this moment, the community will determine who the village leader will be for the next 5 years. Many forms of democratic parties have been held in our current political life. The presidential election (Pilpres), the regional head election (Pilkada) for the Governor, the Regent election (Pilbup) and the Legislative Election (Pileg). Not to forget is the Village Head Election (Pilkades). It is so interesting for me to examine more deeply about the culture of this village head election. However, the party was only a name that rang in the ears of the people of Sampang. Initially this party which was scheduled to be held at the end of 2021, but it was all just a discourse that the community was waiting for, now there is only hope, because with the Sampang Regent Regulation No. 27 of 2021, the fate of the 111 villages affected by this postponement will depend on the Acting Positions appointed by the Sampang Regent. Therefore, many people think that the handling of the village government will not be as conducive as the village head, which the community chooses directly democratically because the election of the village head is elected directly because those who are directly elected have a different sense of responsibility from the Acting (Stakeholders) who Every six months an evaluation must be carried out. The research method used in this study is a qualitative research method with a descriptive approach where the researcher goes directly to the field where the object of research and research instruments are used to collect data is by conducting an observation, interview and documentation. The results of this study are that with the regent's regulation No. 27 of 2021, the simultaneous election of 111 Village Heads will be carried out in 2025, so that Villages that are forced to postpone the Village Head elections will be replaced with Acting Positions. appointed directly by the Regent who was taken from the ASN (State Civil Apparatus) from the Sampang Regency itself. Keywords: Delayed Election of Village Heads in Sampang Regency.